Interpreting music video : popular music in the post-MTV era - Osborn, Brad (New York : Routledge, 2021)
"Interpreting Music Video introduces students to the musical, visual, and sociological aspects of music videos, enabling them to critically analyze a multimedia form with a central place in popular culture. With highly relevant examples drawn from recent music videos across many different genres, this concise and accessible book brings together tools from musical analysis, film and media studies, gender and sexuality studies, and critical race studies, requiring no previous knowledge. Exploring the multiple dimensions of music videos, this book is the perfect introduction to critical analysis for music, media studies, communications, and popular culture. Brad Osborn"--
INTRODUCTION; UNIT 1: INTERPRETING MUSIC; Chapter 1: Form; Chapter 2: Sound Analysis; Chapter 3: Lyrics; UNIT 2: INTERPRETING VISUALS; Chapter 4: Narrative; Chapter 5: Cinematography; Chapter 6: Editing and Special Effects; UNIT 3: INTERPRETING SOCIOLOGY; Chapter 7: Sexuality and Gender Diversity; Chapter 8: Representing Race and Ethnicity; Chapter 9: Music Video and Politics
OCLC-licensed vendor bibliographic record.
Keywords: Music videos -- History and criticism; Music videos -- Social aspects; MUSIC / General; MUSIC / Instruction & Study / Appreciation; MUSIC / History & Criticism